Perancangan Aplikasi Point of Sales Restoran Berbasis Web untuk Perusahaan Summerrice - Frederick, Thomas; Trisnawarman, Dedi; Perdana, Novario Jaya (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Summerrice is a small-scale SME (Small and Medium-sized Enterprise) engaged in the Japanese food and beverage industry. Summerrice restaurant has been in operation since 2018 until 2023. Despite its four years of operation, the restaurant still relies on manual operational records for transactions, inventory, and employee attendance, resulting in a chaotic operational system and significant data loss due to the physical record-keeping that is prone to misplacement. To solve this, a Point of Sales application has been designed to streamline Summerrice restaurant's operational processes, enabling it to run and grow more efficiently with the assistance of this information system program. The development of this program will follow the System Development Life Cycle (SDLC) waterfall model and use the PHP programming language with the CI4 framework, and the database used is MySQL. The application design includes features that facilitate various aspects of the business operations, such as transaction recording, inventory management, and employee attendance.Keywords: Summerrice; Point of Sales; business operations; information systems; effectivenessÂ AbstrakSummerrice adalah perusahaan kecil berskala UMKM yang bergerak di bidang makanan dan minuman Jepang. Restoran Summerrice sudah berjalan semenjak tahun 2018 hingga tahun 2023, walaupun restoran Summerrice sudah berjalan selama 4 tahun namun untuk pencatatan operasional masih dilakukan secara manual seperti transaksi, bahan, dan absensi sehingga membuat sistem pekerjaan sisi operasional dari restoran ini berantakan bahkan banyak data yang hilang dikarenakan pencatatan berbentuk fisik yang mudah hilang. Maka dari itu dirancang sebuah aplikasi Point of Sales untuk dijadikan sistem yang membantu operasional dari restoran Summerrice sehingga restoran dapat berjalan dan berkembang lebih cepat dengan bantuan program sistem informasi ini. Pembuatan program ini akan menggunakan System Development Life Cycle (SDLC) model Waterfall dan menggunakan bahasa pemrograman PHP dengan framework CI4 dan database yang digunakan adalah MySQL.Rancangan aplikasi ini memiliki fitur fitur yang membantu sisi operasional bisnis seperti pencatatan transaksi, bahan bahan, absensi pegawai.Â